The girl behind the wall ebook - Robotham, Mandy (2021)
"A poignant, tender story of families and sisters divided by the cruelty of political chance–my heart ached for them on every page." Kate Quinn, New York Times bestselling author of The Alice Network A city divided.When the Berlin Wall goes up, Karin is on the wrong side of the city. Overnight, she's trapped under Soviet rule in unforgiving East Berlin and separated from her twin sister, Jutta.Two sisters torn apart.Karin and Jutta lead parallel lives for years, cut off by the Wall. But Karin finds one reason to keep going: Otto, the man who gives her hope, even amidst the brutal East German regime.One impossible choice...When Jutta finds a hidden way through the wall, the twins are reunited. But the Stasi have eyes everywhere, and soon Karin is faced with a terrible decision: to flee to the West and be with her sister, or sacrifice it all to follow her heart? From the USA Today and internationally bestselling WWII novelist of The German Midwife, The Secret Messenger and The Berlin Girl comes a story set at the dawn of the Cold War in Berlin. Why readers love The Girl Behind the Wall: 'I was captivated from the very first chapter. It was so well written, I felt like I was really there... A must read.' NetGalley Reviewer 'Oh my goodness, what a page-turner. My heart was in my mouth for most of this book.' NetGalley Reviewer 'Such a fast-paced read! Historical fiction at its best! Highly, highly recommend.' NetGalley Reviewer 'Another fabulous read from the super talented Mandy Robotham who never fails to give us a satisfying story... she has the ability to mix a damn good story with historical facts... you want to read and read... I raced through this one.' NetGalley Reviewer 'What a truly gripping read! I didn't want to stop reading, I was mesmerised...' NetGalley Reviewer 'I couldn't put this book down... well-researched and a heartbreakingly accurate portrayal of the families separated by the wall. Keep the tissues handy because you might need them.' NetGalley Reviewer 'What a read. I found myself thinking of the family in the book as real people I loved. If you read only one book this year, make sure it's this one!' NetGalley Reviewer 'Mandy Robotham has a gift for making history come alive. Amazing read. I simply could not put it down.' NetGalley Reviewer 'Beautifully written and heartfelt... I loved it... A story that will stay with you. Well worth a read.' NetGalley Reviewer 'Another winner from Mandy Robotham!' NetGalley Reviewer